PERAN BUDAYA DALAM MEMPENGARUHI DAYA TARIK DAN DAYA SAING DESTINASI WISATA - Sigit Wibawanto (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2018)
ABSTRACTThe writing of this article aims to see how culture has a role for the country and the region in the development of tourism. Relation approach of tourism and culture is many and varied. Culture touches every aspect of human life and all tourism is considered as cultural tourism. This is because all human movements boost individual culture and generate new knowledge, experience, and meetings among individuals. Today many countries and regions compete to attract people, visitors, and investments. In tourism, traditional factor conditions become the most important element of attraction, both in terms of natural factors (such as beaches, climate, etc.) and the created factors (such as cultural attractions, events, etc.). Therefore, in order to be able to mobilize more from this tourism sector, all these factors must be improved in order to be more effective through industry restructuration, product innovation, and competitiveness. This review shows the conclusions of the importance of culture and tourism as drivers of attractiveness and competitiveness. Most countries and regions are active in developing tangible and intangible cultural assets to develop a comparative advantage of the tourism market. Cultural tourism is one of the fastest and largest in increasing the growth of the global tourism market and the cultural industry, as well as increasingly being used to promote and enhance the competitiveness and attractiveness of the region. The policy implications that can be done are to build partnerships created to support collaboration and build mechanisms to run effectively.Key words: Culture, Tourism, Fascination and Competitiveness